Development of Natural Dyes Practicum Guidelines Based on Local Sasambo Plants: A Study on Identification and Validation - Liswijaya, Liswijaya; Purwoko, Agus Abhi; Hakim, Aliefman; Sukarso, AA; Rokhmat, Joni (Universitas Negeri Semarang, 2025)
This study aims to develop a practicum guidelines for natural dyes based on Sasambo (Sasak, Samawa, Mbojo) indigenous plants to enhance students' understanding of using natural materials as eco-friendly dyes. The environmental hazards posed by synthetic dyes form the background for the importance of this research. The research method used was Research and Development (R&D) with a 4D model approach (Define, Design, Develop, Disseminate). The practicum guidelines includes Sasambo indigenous plants, such as Ruellia Simplex, Curcuma longa, Syzygium cumini, Areca catechu, Pouteria campechiana, Clitoria ternatea, Cajanus cajan, Murraya paniculata, Pandanus amaryllifolius, Ipomoea batatas. Expert validation and lecturer evaluations demonstrated that the developed practicum guidelines for natural dyes based on Sasambo indigenous plants is suitable for use. This is evidenced by its high level of clarity, graphical appeal, and usability, enabling effective student engagement with sustainable practices. Field and laboratory analyses identified ten plants capable of producing vibrant colors, such as purple, yellow, red, orange, blue, black, and green, with added antioxidant and antimicrobial properties. The conclusion of this study is that the developed practicum guidelines can be utilized as an effective learning medium for introducing natural dyes derived from Sasambo indigenous plants, thereby contributing to promoting sustainable industrial practices by leveraging local resources for environmental and economic sustainability.